Insulin Injection Practice and Injection Complications – Results from the Bangladesh Insulin Injection Technique Survey. Issue 1 (2020) - Kamrul-Hasan, ABM; Paul, Ajit Kumar; Amin, Mohammad Nurul; Gaffar, Md Abu Jar; Asaduzzaman, Md; Saifuddin, Mohammad; Mustari, Marufa; Alam, Md Jahangir; Shahid, Mohammad Moin; Nahid-Ul-Haque, KM; Alam, Muhammad Shah; Rahman, Md Motiur; et al.
No abstract available